Screen for MicroRNA and Drug Interactions in Breast Cancer Cell Lines Points to miR-126 as a Modulator of CDK4/6 and PIK3CA Inhibitors - Baldassari, Federica; Zerbinati, Carlotta; Galasso, Marco; Corrà, Fabio; Minotti, Linda; Agnoletto, Chiara; Previati, Maurizio; Croce, Carlo M.; Volinia, Stefano (Frontiers in Genetics, 2018)
Background: Breast cancer (BC) represents the most common cancer in women worldwide. Due to its heterogeneous nature, breast cancer management might benefit from differential treatments towards personalized medicine. Additionally, drug resistance is a common phenomenon. We systematically investigated the effect of 14 different drugs administered on BC cell lines in combination with microRNAs (miRNA, miR). Methods: Thirty-eight miRNAs, all associated with BC by clinical and molecular parameters including progression, prognosis and subtypes, were tested for their effects on the viability of 12 different BC cell lines. Four miRNAs with the strongest impact on viability were further assayed in combination with 14 BC drugs. Mann-Whitney U test with Bonferroni correction was used for statistical analysis. Results: In a miRNA only pre-screen we observed effects on BC cell lines’ viability for 34 out of 38 candidate miRNAs. We then identified 14 miRNA/drug combinations for which the combination IC50 was lower than that of both miRNA and drug as single agents. miR-181a, paired with GSK1070916, Doxorubicin, XL765 and AMG511, was the only miRNA active on the triple negative (TNBC) MDA-MB-468 cell line. miR-126 was the only miRNA (in combination with CDK4/6 or PIK3CA inhibitors) with significant effects on cell lines from different subtypes: MCF7 (Luminal) and MDA-MB-453 (HER2+). Because of its activity on different BC subtypes, we investigated the genome wide effects of miR-126 using transcriptomics and confirmed that expression of miR-126 in BC affected cell cycle and mitosis. Conclusion: Our results show that a combination treatment with miRNAs, in particular miR-181a, miR-326, miR-9 and miR-126, enhance the activity of specific BC drugs in vitro, even on the most aggressive BC subtypes, HER2+ and TNBC. Finally, as expected from its drug interactions, based on a whole transcriptome study we could confirm a role for miR-126 in cell cycle regulation.